African Indigenous Epistemologies, Traditions, and Practices Before the Arrival of Europeans - Ernestina Wiafe (Educational Considerations, 2023)
Africa is the second-largest continent in the world (after Asia), making up around one-fifth of the planet’s land area. There are many different cultural and linguistic groupings, because of how long humans have lived there. Due to this, Africans have a network of knowledge, beliefs, and traditions that they use to preserve, explain, and contextualize their ties with their culture and environment before the arrival of Europeans. Formal and informal transfers of indigenous knowledge took place between families, tribes, and communities through social contacts, oral traditions, ceremonial acts, and other activities. I will indicate, with all these indigenous systems and ways of life, the Europeans and other foreign settlers to the areas of Africa labeled the cherished traditional ways of teaching and learning of the native people as primitive and referred to the indigenous as uneducated, savage, and uncultured. It is therefore important to tell the story so that those who mismanage our affairs would not silence our criticism by pretending they have facts not available to the rest of us because, as Cinua Achebe stated, “Until the lions have their historians, the history of the hunt will always glorify the hunter.”
Keywords: Alkebulan; Africa; Indigenous Knowledge; and Indigenous Traditions